Zainullah Kurikulum 2013 antara Ideal dan Real - ZAINULLAH, ZAINULLAH (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
Ideal curriculum is the curriculum that consists of something good as the dream of book of curriculum. Real curriculum is real actions that apply in learning and teaching process as the real of the planing curriculum. Curriculum content is what we have to do to the learners and the learning and teaching is a manner of what we will give or teach to the learners. The development of 2013 curriculum is stresset to compeletness of learners thinking, the impressing of curriculum management, the domination and development of material, stressing process of teaching and learning process, and lining appropriate of learning responsibility in order to get the guaranty of appropriate between what we want and what we get. Effected aspect to the implementation of 2013 curriculum raleted directly to the process of learning, namely: teachers’ creativities, learners’ activities, facilities and recourses.Will the 2013 curriculum can be realized by teachers practically in the field? Today, the changing of curriculum reap many responses, some people are pessimistic even declining the curriculum, but at the same time some are appreciative to the curriculum. The changing of curriculum does not affect the changing of the teacher’s method and style to teach. It needs revolutionary change in the practice of 2013 curriculum.